Pengaruh Kepemimpinan, Kompensasi, Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Charoen Popkhand Indonesia Tbk (CPI) - Ependi Ependi (Ilmu Ekonomi Manajemen dan Akuntansi, 2020)
Influence Leadership, Compensation, Motivation and Work Discipline Against Employee Performance PT. Charoen Popkhand Indonesia Tbk (CPI). This study aims to determine the effect of Leadership, Compensation, Motivation and Work Discipline Against Employee Performance PT. Charoen Popkhand Indonesia Tbk (CPI).Sample response taken by purposive sampling method where samples taken as much as 55 respondents from 55 Employees of PT. Charoen Popkhand Indonesia Tbk (CPI). The analysis method used in this research is multiple linear regression analysis and classical assumption test. Hypothesis testing is done by using F test and t test.The results of this study show that partially, Leadership variables have a low and insignificant effect on employee performance, Compensation has an effect on and Significantly to Employee Performance, Motivation influence and significant to Employee Performance Meanwhile, and Discipline also influential and significant to Employee Performance. Taken together, Leadership, Compensation, Motivation and Discipline significant effect on Employee Performance PT. Charoen Popkhand Indonesia Tbk (CPI).Keywords:  Employee Performance is instrument achievement that must be set by PT. Charoen Popkhand Indonesia Tbk (CPI).